Sub-Acute Toxicity Effects of Methanolic Stem Bark Extract of Entada abyssinica on Biochemical, Haematological and Histopathological Parameters in Wistar Albino Rats - Obakiro, Samuel Baker; Kiprop, Ambrose; Kigondu, Elizabeth; K’owino, Isaac; Kiyimba, Kenedy; Drago Kato, Charles; Gavamukulya, Yahaya (Frontiers in Pharmacology, 2021)
Whereas the efficacy of Entada abyssinica (fabaceae) extracts against various ailments has been scientifically validated, its safety has not been established. This study was undertaken to evaluate the toxicity effects of methanolic stem bark extract of E. abyssinica on biochemical, haematological and histological parameters of Wistar albino rats following repeated oral administration. Wistar albino rats of both sexes were randomized into groups and orally administered daily with determined doses (150, 300 and 600 mg/Kg) of E. abyssinica methanolic extract using distilled water as a control for 28 days. On the 29th day, all the animals were sacrificed and dissected to collect blood and selected organs. The serum and whole blood were assayed for biochemical and haematological parameters respectively while selected organs were examined for histopathological lesions. Numerical data was analyzed using graph pad prism and expressed as mean ± standard error of mean. The differences between the treatment and control groups were tested for statistical significance using one-way analysis of variance and/or Student's t-test. In repeated daily oral doses (150, 300 and 600 mg/Kg), the methanolic stem bark extract of E. abyssinica did not cause significant alteration in majority of the biochemical and hematological indices. However, the extract significantly elevated the level of uric acid (all doses), aspartate aminotransferase (300 and 600mg/Kg), low density lipoproteins (150mg/Kg) and mean corpuscular heamoglobin concentration (all doses). On the other hand, the extracts reduced high density lipoproteins (150 and 300mg/kg), mean corpuscular volume (all doses), haematocrit (150 and 600mg/Kg), mean platelet volume (150 and 600mg/Kg) and procalcitonin (150mg/Kg). In the vital organs, there were no significant lesions observed except at the highest dose (600 mg/kg) where there was mild evidence of lymphocyte infiltration in the liver and focal interstitial nephritis. In conclusion, the methanolic stem bark extract of E. abyssinica is relatively safe in Wistar albino rats when repetitively administered orally in small doses for a prolonged period of time. We recommend more chronic toxicity studies and clinical trials on herbal remedies containing this plant to ensure that its use is free of potential toxicity to humans.